Дослідження властивостей початкового і переброженого в біогазових установок рідинно-плинного гною врх та його попереднє зневоднення методом центрифугування - Шеліманова, О. В.; Шпільберг, Л. Ю.; Михалевич, В. В.; Корбут, Н. С.; Стецюк, В. Г.; Коханенко, М. С. (Енергетика і автоматика, 2017)
INVESTIGATION OF THE PROPERTIES OF THE ORIGIN AND BROKEN IN THE BGP THE CATTLE FARMS’ LIQUID-PLANE MANURE AND ITS PREVIOUS DEHYDRATION BY THE CENTRIFUGATION METHOD O. Shelimanova, L. Shpilberg, V. Mikhalevich, N. Korbut, V. Stetsyuk, M. Kohanenko Ukraine has a significant potential for resource-rich waste (biogas and broken mass), which are formed in biogas plants due to the fermentation of agricultural products. On the basis of these wastes it is possible to deploy a powerful production of organic fertilizers, but today there is an obvious lag behind developed countries. This determines the relevance of this study. The main trends of world agricultural production are: 1.The advantage of introducing organic fertilizers; 2. More stringent environmental standards; 3. More rational introduction of mineral fertilizers In European countries, the annual application of organic fertilizers increases, and mineral decreases: ● nitrogen at 6%; ● phosphorus by 14 %; ● potassium by 12 %. The use of biofertilizers is especially important for the reproduction of soil organic matter, restoration of fertility and the build-up of the humus component, especially after growing energy crops. The purpose of the study is to obtain data for the development of the technology for waste treatment of BGP of modern livestock complexes in dry granulated biofertilizer, feed and solid biofuel. Experimental studies of the physical and mechanical characteristics of the initial ones were carried out and liquid-flowing wastes were transferred to BGP and preliminary partial dehydration of them by increasing the content of absolutely dry matter in a dispersed medium. On the basis of the received physicochemical characteristics of the overburdened and initial dispersion of manure of the cattle, correction of the work of the BSU was carried out. It has been proved that preliminary separation of the carrier phase by centrifugation method allows to increase the content of absolute dry matter by several times and, accordingly, to reduce the necessary expenditure of thermal energy for evaporation with further dehydration. The achieved values of the content of absolutely dry matter allow us to recommend to investigate the possibility of further mechanical separation of the liquid with the help of screw presses, including with the use of solid fillers, and only then go to the heat-drying.